2017
DOI: 10.22377/ijgp.v11i02.917
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Background and Aim of Study: The main aim of this research is to establish a standardized data regarding its safety through including certain parameters. Kadali (Musa paradisiaca) Linn. (Musaceae) is a perennial herb which is like a tree and is used in Ayurvedic system of medicine to cure many diseases. Materials and Methods: In the present study, pharmacognostical and phytochemical standardization of plant material was performed as per the guidelines of World Health Organization. Results: The stamen of M. par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The physicochemical measurements of the of Musa paradisiaca stamen were (w/w): loss on drying (5.5%), total ash (5.81%), water-soluble ash (3.79%), acid-insoluble ash (2.61%), water-soluble extractive (7.17%), methanol soluble extractive (2.38%), hexane soluble extractive (1.44%), ethyl acetate soluble extractive (2.24%), and petroleum ether soluble extractive (4.0%) (ASHISH et al, 2017).…”
Section: Physicochemical Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The physicochemical measurements of the of Musa paradisiaca stamen were (w/w): loss on drying (5.5%), total ash (5.81%), water-soluble ash (3.79%), acid-insoluble ash (2.61%), water-soluble extractive (7.17%), methanol soluble extractive (2.38%), hexane soluble extractive (1.44%), ethyl acetate soluble extractive (2.24%), and petroleum ether soluble extractive (4.0%) (ASHISH et al, 2017).…”
Section: Physicochemical Characteristicsmentioning
confidence: 99%
“…The preliminary phytochemical analysis of various parts extracts of Musa paradisica showed that the plant contained carbohydrates, reducing sugar, tannins, saponins, alkaloids, glycosides, steroids, phytosterols, phenols, flavonoids and terpenoids (KIBRIA et al, 2019;ASHISH et al, 2017;MAHMOOD et al, 2011).…”
Section: Chemical Constituentsmentioning
confidence: 99%